Alzheimer and Parkinson diseases, frontotemporal lobar degeneration and amyotrophic lateral sclerosis overlapping neuropathology start in the first two decades of life in pollution exposed urbanites and brain ultrafine particulate matter and industrial nanoparticles, including Fe, Ti, Al, V, Ni, Hg, Co, Cu, Zn, Ag, Pt, Ce, La, Pr and W are key players. Metropolitan Mexico City health crisis is in progress - Calderón-Garcidueñas, Lilian; Stommel, Elijah W.; Torres-Jardón, Ricardo; Hernández-Luna, Jacqueline; Aiello-Mora, Mario; González-Maciel, Angélica; Reynoso-Robles, Rafael; Pérez-Guillé, Beatriz; Silva-Pereyra, Héctor G.; Tehuacanero-Cuapa, Samuel; Rodríguez-Gómez, Arturo; Lachmann, Ingolf; et al. (Frontiers in Human Neuroscience, 2024)
The neuropathological hallmarks of Alzheimer's disease (AD), Parkinson's disease (PD), frontotemporal lobar degeneration (FTLD) and amyotrophic lateral scleroses (ALS) are present in urban children exposed to fine particulate matter (PM2.5), combustion and friction ultrafine PM (UFPM) and industrial nanoparticles (NPs). Autopsy studies strongly suggests in cases from Metropolitan Mexico City (MMC) that anthropogenic UFPM and industrial NPs, reach the brain through the nasal/olfactory, lung, gastrointestinal tract, skin and placenta barriers. Diesel heavy unregulated vehicles are a key UFPM source for 21.8 million MMC residents. We found that hyperphosphorylated tau, beta amyloid1-42, α-synuclein and TAR DNA-binding protein-43 were associated with NPs in 186 forensic autopsies (mean age 27.45±11.89 y).The neurovascular unit is an early NPs anatomical target and the first two decades of life are critical: 100% of 57 children age 14.8±5.2y had AD pathology; 25 (43.9%) AD+TDP-43;11 (19.3%) AD + PD + TDP-43 and 2 (3.56%) AD +PD.